Applying the HCVF toolkit to assess the conservation value of Gunung Singai, Sarawak, East Malaysia - Tuen, Andrew A.; Alexander Kiew, Sayok; Indraneil, Das; Tonga, Noweg; Charlie, J. Laman; Les, Met (Universiti Malaysia Sarawak (UNIMAS), 2014)
The HCVF Toolkit for Malaysia was primarily developed to help forest managers comply with Principle 9 in both the Forest Stewardship Council and the Malaysian Criteria and Indicators for Forest Management Certification. These are standard adopted by the National Steering Committee for certification of natural forests in Malaysia. Here, we use it to assess the conservation value of Gunung Singai, an isolated mountain massif in western Sarawak. Based on Criteria HCV 1.2 (Threatened and Endangered Species), HCV1.3 (Endemism), HCV4.1 (Watershed Protection), HCV4.2 (Erosion Control), HCV5 (Basic Needs of Local Communities) and HCV6 (Cultural Identity of Local Communities) Gunung Singai is found to have high ecological and cultural values and warrant management and conservation.